Phytochemical Analysis and Antioxidant Activity of Pandila Tree Leaves (Saurauia Tristlyla Dc) From Tibo Village - Abdul Hapid; Asniati; Ariyanti; Erniwati; Muthmainah; Naldiyanto Madao (Tadulako Science and Technology Journal, 2024)
Introduction: The Pandila tree known as pandila (Saurauia tristlyla DC) is one of the plants that has been traditionally used as a medicinal material. Pandila has been traditionally used by the community as a medicine for external and internal diseases, for example, pandila leaves are believed by the Tibo Village community to absorb congealed blood due to accidents. This study aims to determine the secondary metabolite content and antioxidant activity of pandila leaves. Method: The research method used in this study is a descriptive method by looking at changes in color and liquid form in alkaloids, Flavonoid, Tannin, Saponin, Steroid, Terpenoid, and Carotenoid compounds. Phytochemical analysis was carried out on 96% ethanol extract of pandila leaves. The DPPH method was used to determine the antioxidant activity. The results of phytochemical analysis obtained on the leaves of Pandila tree leaves (Saurauia Tristlyla DC) using 96% ethanol solvent are old leaf extracts and young leaves of pandila positively contain 3 compounds namely Tannins, Steroids, and Carotenoids. Results and Discussion: The results of the antioxidant activity test of Pandila leaf extract using the DPPH method on old leaves have an IC50 of 101, 2844 ppm including in the moderate category, and on young leaves have an IC50 of 76.688 ppm which is included in the strong category. Conclusion: Pandila tree leaves are still safe to be used as traditional medicine, by looking at the tannin, steroid, and carotenoid compounds contained in pandila leaves. In addition, the results of antioxidant activity analysis are also a supporting factor where the antioxidant content in old leaves and young leaves of Pandila trees is classified as strong and moderate, so this plant is still safe to be used as a traditional medicinal plant.